A COMMUNITY-BASED SURVEY TO ASSESS THE PREVALENCE AND ETIOLOGICAL FACTORS FOR TYPE II DIABETES MELLITUS IN THE TWO REGIONAL STATES OF SOUTHERN INDIA–A PILOT STUDY - RAO, P. SAILAJA; BUTOOL, SANA; MANIYAR, SHIRAZ AHMED; TUNNISA, FAZEELA; ALI SOHAIL, MOHAMMED; ALI, MOHAMMED MUKKARAM; TAHSEEN, BHUSHRA (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: The concurrent study aimed to assess and analyse the prevalence and etiological factors responsible for the occurrence of Type 2 diabetes mellitus among the labour population. A cross-sectional study was conducted among the labour in the two regional states of southern India. This study was conducted for 6 mo in the two states of the southern region of India. Methods: A questionnaire was designed with various questions to study the prevalence and scrutinize the causes responsible for the occurrence of type 2 diabetes among the labour population. A total number of n=104 respondents participated, out of which 57 were diabetic and were further analysed. The results were compiled and subjected to the statistical analysis (Chi-square test). Results: In the demographics, the majority of the participants were females (n=33), while the remaining were males. 75% of the participants were with age groups between 31-60 y, about 50% were uneducated and belonged to lower income category. Etiological factors like family history (>50%) and comorbid conditions (n=43) were more responsible for the prevalence of Type 2 diabetes. In the food habits assessment, carbohydrates and non-vegetarian consumption were more in majority (>45%) of the respondents. 86% of the participants were on medication, along with only 57.8% were recorded with HbA1c. Diet restrictions and timely intake of food were up to the level after the diagnosis of the disease. Nearly 50% of diabetics were confident about the management of the disease and 54 respondents were spotted to have a keen interest in acquiring knowledge further. Conclusion: The findings concluded that the diabetic participants followed the necessary diet requirements and were on medication for the treatment of type 2 diabetes mellitus.